China and North Korea’s Missiles: Having the Cake and Eating It? - Nah, Liang Tuang (2016)
Beijing bitterly opposes the deployment of US missile defence systems in South Korea, but unless it is prepared to implement sanctions which would seriously punish Pyongyang’s missile aggrandisement, such deployments are inevitable.